The probability of a scaffolding failure on a construction site. (January 2022) - Błazik-Borowa, Ewa; Geryło, Robert; Wielgos, Piotr
Graphical abstract: Highlight: The method for assessing the technical conditions of scaffolds used on construction sites. Inventory of scaffolds and full-scale measurements of their loads. Finite elements static analyses of scaffolds which are subjected to real loads. Scenarios of scaffolding failures. The probability of a scaffold failure at maximum loads. Abstract: The paper presents a method of determination for the probability of a scaffold failure at maximum loads which are measured in one week. The research concerns scaffolding which were used on construction sites. The method assumes that the geometries (including imperfections) are deterministic and are compliant with the conditions measured on the construction site. The material properties of the scaffolding components, which cannot be measured, are generated from the normal distribution. Failure is treated as a random event occurring when one component or a group of components fails. The failure event is described by a set of serial diagrams concerning stands, transoms, and additional elements, as well as a mixed diagram concerning a wall anchoring. Probabilities of a failure were determined for 120 scaffolding and their values were obtained in a range from 10 -9 to almost 10 0 . A positive or negative evaluation of the scaffolding depends on the level of the acceptable risk of failure. If reliability predictor (parameter similar to reliability index) is equal to 4.7, 41% of the scaffolds used for 12 weeks do not ensure safety of construction workers. If the reliability predictor is equal to 3.5, the percentage of unsafe scaffolds is 17%. The presented results concern frame scaffolds, erected next to elevations and forming planes. It is probable that for frame scaffolds with more complex geometries and modular scaffolds, the results will be different.